SOCIO-PERSONAL FACTORS AS PREDICTORS OF PSYCHOLOGICAL WELL-BEING OF PUPILS WITH MILD INTELLECTUAL DISABILITY IN THE SOUTH-WEST, NIGERIA (2023)
Psychological well-being, a core feature of mental health that describes an individual’s emotional state, is an indication for good quality of life. Reports show that many pupils with mild intellectual disability in the south-west, Nigeria usually experience deficits in psychological well-being. Previous studies focused more on the acquisition of functional academic and adaptive skills of Pupils with Mild Intellectual Disability (PsMID) than on socio-personal factors (self-esteem, social competence, loneliness and aggression) influencing their psychological well-being. This study, therefore, was carried out to investigate the socio-personal factors (self-esteem, social competence, loneliness, home background, depression, aggression and anxiety) as predictors of psychological well-being of pupils with mild intellectual disability in the South-west, Nigeria. Ryff’s Psychological Well-being and Vygotsky’s Socio-cultural theories provided the framework, while the study adopted the descriptive design of the correlational type. The multi-stage sampling procedure was used. The six states in the south-west, Nigeria were enumerated. The purposive sampling technique was adopted to select 28 government-owned primary special schools within the six states. Based on the Slosson Intelligence Test-Revised, 350 PsMID with intelligence quotient of 52-68 were selected. The instruments used were Slosson Intelligence Test-Revised (r=0.86), Home Background Questionnaire (r=0.75), Self-esteem (r=0.75), Social Competence (r=0.90), Loneliness (r=0.83), Depression (r=0.75), Aggression (r=0.72), Anxiety (r=0.87) and Psychological Well-being (r=0.75) rating scales. Data were analysed using descriptive statistics, Pearson product moment correlation and Multiple regression at 0.05 level of significance. The respondents’ age was 14.48±3.43 years, and 53.4% were male. The respondents’ states of residence were Oyo (38.9%); Osun (20.3%); Lagos (18.9%); Ogun (8.0%); Ekiti (7.1%) and Ondo (6.9%). The respondents’ levels of aggression (x ̅=2.57) and self-esteem (x ̅=2.55) were high against the threshold of 2.50, as well as their levels of anxiety (x ̅=1.97) and social competence (x ̅=2.20) against the threshold of 1.50 respectively; while their levels of loneliness (x ̅ =2.43) and depression (x ̅=2.31), were low against the threshold of 2.50. Social competence (r = 0.23) had a significant positive relationship, while loneliness (r = -0.18) had a significant negative relationship with psychological well-being of PsMID. There was a significant joint contribution of the independent variables (self-esteem, social competence, loneliness, home background, depression, aggression and anxiety) to the psychological well-being of PsMID (F (7; 342) = 4.85; Adj. R2 = 0.072), accounting for 7.2% of its variance. Social competence (β=0.22), loneliness (β= -0.17), and aggression (β=0.12) had significant contributions to the prediction of psychological well-being of PsMID. Social competence positively influenced the psychological well-being of pupils with mild intellectual disability in the south-west, Nigeria, while loneliness negatively influenced their psychological well-being. Special educators, caregivers, parents and school administrators should pay attention to these factors to ensure optimal psychological well-being among pupils with mild intellectual disability.